LANGUAGE STYLE BETWEEN PUBLIC SPEAKERS IN PUBLIC SPEAKING PERFORMANCES - Rizky Satria; Hamzah Hamzah; Fitrawati Fitrawati (English Language and Literature, 2018)
Although there have been many studies show that different style in using language, there are very few studies that compare language style in public speaking through three levels of metafunction. This study aims to compare the differences and the similarities between two public speakers in 1) the level of ideational metafunction, 2) the level of interpersonal metafunction, and 3) the level of textual metafunction. This is comparative study within qualitative approach. The results of the study show that they share three similarities and two differences in the level of ideational metafunction. Then, there are six similarities and four differences in the interpersonal level. Meanwhile, there are four similarities and two differences found for textual metafunction. The conclusion obtained from the findings is that they are more similar rather than different and the differences in style are affected by the differences in cultural background of the speakers which are represented through speech and lead to the different ways of producing structure of clauses and selection of words in the three levels of metafunction.